HIV-infected progressors and long-term non-progressors differ in their capacity to respond to an A-class CpG oligodeoxynucleotide - Saez, Raquel; Echaniz, Pilar; de Juan, Maria Dolores; Iribarren, José Antonio; Cuadrado, Emilio (AIDS (London), 2005)
We used an A-class CpG oligodeoxynucleotide to explore innate immunity in HIV infection and observed that natural killer cells from progressors showed a markedly lower IFN-gamma production in response to the oligonuclotide as compared with long-term non-progressing subjects and healthy HIV-negative individuals. This functional defect was found in patients who showed a long immunological reduction and in those who had had a recent reduction in their CD4 cell counts.